Pengolahan Limbah Jagung untuk Pakan Ternak - Anugrah, Rinasa Agistya; Ramadhan, Cahyo Setiadi (Universitas Muhammadiyah Yogyakarta, 2019)
Corn is one of the main agricultural plant commodities in Gunung Kidul regency especially Saptosari village because this area has high result potential and production of corn. That high potential is in line with its high waste produced such as its leaves, stalks, cobs, and husks. To date, the leaves and stalks are corn wastes that have been used as fresh cattle feed, while the cobs are only thrown away or burnt. In fact, all corn wastes can be used as dry cattle feed that can be stored. The potential to process corn waste is important by noting the number of cattle in Saptosari village and Gunung Kidul regency in general to meet the high demand of cattle feed. This type of cattle feed is very needed in dry season due to the shortage of fresh cattle feed. As a result, there is a need to have a society empowerment activity in Saptosari village especially in Tukuk hamlet aimed at developing the society’s skills to process corn waste into cattle feed. The method of empowerment activity was done in stages that include socialization, training, and waste processing practicum. The success of society empowerment activity that was implemented is shown by the increasing knowledge and skills of the society in processing the corn waste into cattle feed. The most significant finding is that the society is very enthusiastic in processing the corn waste into cattle feed shown by self-procurement of corn waste crusher machine.